Threat Hunting and Advanced Persistent Threats (APTs): A Comprehensive Analysis - Srikanth Bellamkonda (International Journal of Intelligent Systems and Applications in Engineering, 2021)
In the evolving landscape of cybersecurity, Advanced Persistent Threats (APTs) represent one of the most sophisticated and persistent forms of cyberattacks. These threats are characterized by their stealthy nature, prolonged duration, and targeted approach, often aiming to steal sensitive information or disrupt critical infrastructure. Traditional security measures, such as firewalls and antivirus software, are increasingly inadequate in detecting and mitigating APTs. This paper explores the role of threat hunting as a proactive defense mechanism against APTs. It delves into the methodologies, tools, and strategies employed in threat hunting, emphasizing the importance of human expertise and advanced technologies like artificial intelligence (AI) and machine learning (ML). Through a comprehensive literature review and analysis of real-world case studies, the study highlights the effectiveness of threat hunting in identifying and neutralizing APTs. Additionally, the research addresses the challenges and limitations associated with threat hunting and proposes best practices for organizations to enhance their cybersecurity posture. The findings underscore the critical need for a proactive and intelligence-driven approach to combat the ever-evolving threat landscape dominated by APTs.